Lung eosinophils increase vagus nerve-mediated airway reflex bronchoconstriction in mice - Nie, Zhenying (Am J Physiol Lung Cell Mol Physiol, 2020)
Eosinophils mediate airway hyperresponsiveness by increasing vagally mediated reflex bronchoconstriction. Here, we tested whether circulating or airway eosinophils change nerve function. Airway resistance in response to aerosolized 5-hydroxytryptamine (5-HT, 10–300 mM) was measured in wild-type mice or transgenic mice that overexpress IL5 in T cells (+IL5(T)), overexpress IL5 in airway epithelium (+IL5(AE)), or overexpress IL5 but are devoid of eosinophils (+IL5(AE)/−Eos). Inflammatory cells in bronchoalveolar lavage (BAL), blood, and bone marrow were quantified. Blood eosinophils were increased in +IL5(T) and +IL5(AE) mice compared with wild-type mice. +IL5(T) mice had increased eosinophils in bone marrow while +IL5(AE) mice had increased eosinophils in BAL. Eosinophils surrounding large airways were significantly increased only in +IL5(AE) mice. With intact vagal innervation, aerosolized 5-HT significantly increased airway resistance in +IL5(AE) mice. 5-HT-induced bronchoconstriction was blocked by vagotomy or atropine, demonstrating that it was mediated via a vagal reflex. Airway resistance was not increased in +IL5(AE)/−Eos mice, demonstrating that it required lung eosinophils, but was not affected by increased bone marrow or blood eosinophils or by increased IL5 in the absence of eosinophils. Eosinophils did not change M3 function on airway smooth muscle, since airway responses to methacholine in vagotomized mice were not different among strains. Eosinophils surrounding large airways were sufficient, even in the absence of increased IL5 or external insult, to increase vagally mediated reflex bronchoconstriction. Specifically blocking or reducing eosinophils surrounding large airways may effectively inhibit reflex hyperresponsiveness mediated by vagus nerves in eosinophilic asthma.